Lysosomal Storage Disease-Associated Neuropathy: Targeting Stable Nucleic Acid Lipid Particle (SNALP)-Formulated siRNAs to the Brain as a Therapeutic Approach: The Sanfilippo Syndrome example - Coutinho, Maria Francisca (2020)
More than two thirds of Lysosomal Storage Diseases (LSDs) present central nervous system (CNS) involvement. Nevertheless, only one of the currently approved therapies has an impact on neuropathology. Therefore, alternative approaches are under development, either addressing the underlying enzymatic defect or its downstream consequences. Amongst those LSDs with a marked CNS phenotype, Mucopolysaccharidosis type III, or Sanfilippo syndrome, is a hallmark example of an LSD in desperate need for an effective brain-targeted therapeutic approach. One of the alternative therapeutic approaches for Sanfilippo syndrome, which is under study by different teams, relies on an attempt to block substrate accumulation upstream, by promoting a decrease of its synthesis. This concept is known as substrate reduction therapy and may be triggered by several molecules, such as small interfering RNAs (siRNAs). siRNAs promote RNA interference, a naturally occurring sequence-specific post-transcriptional gene-silencing mechanism, and may target virtually any gene of interest, inhibiting its expression. Still, naked siRNAs have limited cellular uptake, low biological stability, and unfavorable pharmacokinetics. Thus, their translation into clinics requires proper delivery methods. One promising platform is a special class of liposomes called stable nucleic acid lipid particles (SNALPs), which are characterized by high cargo encapsulation efficiency and may be engineered to promote targeted delivery to specific receptors. Here, we review the concept of SNALPs, presenting a series of examples on their efficacy as siRNA nanodelivery systems. By doing so, we hope to unveil the therapeutic potential of these nanosystems for targeted brain delivery of siRNAs in LSDs, with a particular focus on the Sanfilippo syndrome.